2000
DOI: 10.1063/1.126606
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and magnetic properties of single-crystal Co2MnGe Heusler alloy films on GaAs (001)

Abstract: Single-crystal Co2MnGe Heusler alloy films were epitaxially grown on GaAs (001) substrates by molecular beam epitaxy. In situ reflection high-energy electron diffraction patterns and Auger spectroscopy confirmed the high-quality growth and stoichiometry. At 5 K, a saturation magnetization of 1000 emu/cm3 was measured. In-plane ferromagnetic resonance shows narrow linewidths and four-fold plus uniaxial anisotropy. A room-temperature resistivity of 115 μΩ cm has also been determined. The temperature dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 18 publications
11
72
2
Order By: Relevance
“…This can be explained by a model in which ͑i͒ uniaxial anisotropy imposed by the GaAs symmetry with an easy axis of either the GaAs͓110͔ or ͓1−10͔ direction and ͑ii͒ cubic anisotropy imposed by the Co 2 YZ with easy axes of Co 2 YZ͗110͘ are superimposed. [14][15][16] In our case, the easy axis direction of the uniaxial anisotropy was along the GaAs͓1−10͔ direction. When the MgO interlayer was inserted, the uniaxial anisotropy was weakened ͓Fig.…”
Section: Methodsmentioning
confidence: 69%
“…This can be explained by a model in which ͑i͒ uniaxial anisotropy imposed by the GaAs symmetry with an easy axis of either the GaAs͓110͔ or ͓1−10͔ direction and ͑ii͒ cubic anisotropy imposed by the Co 2 YZ with easy axes of Co 2 YZ͗110͘ are superimposed. [14][15][16] In our case, the easy axis direction of the uniaxial anisotropy was along the GaAs͓1−10͔ direction. When the MgO interlayer was inserted, the uniaxial anisotropy was weakened ͓Fig.…”
Section: Methodsmentioning
confidence: 69%
“…14͒ or other Heusler materials on GaAs. 15,17 This can be explained with the model in which ͑i͒ uniaxial anisotropy imposed by the GaAs symmetry with an easy axis of either the ͓110͔ GaAs or ͓1 −10͔ GaAs direction and ͑ii͒ cubic anisotropy imposed by the CCFA with easy axes of ͗110͘ CCFA are superimposed. 17,18 In our case, the uniaxial anisotropy with its easy axis in the ͓110͔ GaAs direction was dominant compared to the cubic anisotropy, as we will later show.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…But Brown et al [30] using polarized neutron diffraction measurements have shown that there is a finite very small spin-down DOS at the Fermi level instead of an absolute gap. Recently, Ambrose et al managed to grow a Co 2 MnGe thin film on a GaAs(001) substrate by molecular beam epitaxy [31], and Geiersbach et al grew by sputtering (110) thin films of Co 2 MnSi, Co 2 MnGe and Co 2 MnSn using a metallic seed on top of a MgO(001) substrate [32].…”
Section: Introductionmentioning
confidence: 99%